Identificar las principales enfermedades del cultivo de rábano (Raphanus sativus) - Coello Figueroa, Brayan Steven (2022)
The production of the radish crop can be affected by several factors, among them, the attack of different microorganisms. This can cause large losses in production, reducing the yield and quality of the bulbs that produce the crop. In Ecuador there are approximately 14,455 cultivated hectares of radish, the main producing provinces are located in the north of the country such as Imbabura, Tungurahua, Cotopaxi and Chimborazo. The main phytosanitary problem in radish cultivation is downy mildew (Peronospora parasitica), fungal wilt, leaf septoria, fusarium, downy mildew and black rot. These diseases are common during the months with the highest incidence of humidity. It appears in the form of small yellow spots on the leaves, necrosis and later, after a period of time, these spots turn dark brown, ending up drying them completely, causing between 25 and 75% of the production, postponing the fulfillment of the market demand regarding the quality of radish bulbs, causing rejection in the destination market. On the other hand, in the region where radish cultivation is developed, which is in areas with temperate climates, taking into account that the crop must be protected during times of high temperatures. The crop cycle depends on the climatic conditions, being able to find from 20 days to more than 70 days. Frost occurs at -2ºC. Vegetative development takes place between 6ºC and 30ºC, the best is between 18-22ºC. The optimum germination temperature is between 20-25ºC. It adapts to any type of soil, although it prefers deep, clayey and neutral soils. The pH must range between 5.5 and 6.8. It does not tolerate salinity. In summer, the small roots are harvested after 45 days, the medium ones about 10 days later and the large ones after 70-80 days